Correlation and regression analysis of FA2H and ELOVL3 functional genes for cashmere fineness with production performance in Liaoning cashmere goat - Shuaitong Li; Lingchao Kong; Siyi Li; Yining Liu; Yuan Pan; Qingkun Liu; Weihang Hong; Hua Ma; Qingyu Yuan; Ran Duan; Qiying Zhan; Zeying Wang (Journal of Genetic Engineering and Biotechnology)
Liaoning cashmere goat (LCG) is characterized by the highest individual cashmere yield, but its cashmere fineness tends to be coarse. Therefore, our research primarily focuses on reducing cashmere fineness. Through lipidomics screening and identification, we identified the crucial functional genes FA2H and ELOVL3 associated with cashmere fineness. Subsequently, using PCR-seq, we conducted gene typing and SNP analysis on the experimental population DNA, In the FA2H gene, a SNP locus T42443G was detected in LCG buck, with the TT genotype showing advantageous traits in cashmere fineness, meat quality, and body size, while the TG genotype demonstrated advantages in slaughter performance,In LCG doe, the TG genotype shows advantageous traits in cashmere fineness, milk production, and meat quality, while the TT genotype exhibits advantages in slaughter performance, lambing, and body size. In the ELOVL3 gene, a SNP locus C2133A was identified in LCG buck, where the CC genotype was advantageous for cashmere fineness, Only CA genotype was found in slaughter and meat quality. Additionally, and the CA genotype showed superiority in body size. On LCG doe, The CC genotype was the advantageous genotype in terms of cashmere fineness, milk production, slaughter performance, and meat quality. The CA genotype was the advantageous genotype in terms of lambing and body size. The dominant genotypes identified to influence both doe cashmere fineness and slaughter performance were TT and CC. The identified dominant haplotype combination for cashmere production performance in LCG was CCTG. The dominant haplotype combination for doe slaughter performance was the CCTT haplotype combination. The dominant haplotype combination for buck slaughter performance was the CATG haplotype combination. Therefore, the TT genotype of the FA2H gene and the CC genotype of the ELOVL3 gene in LCG buck, and the TG genotype of the FA2H gene and the CC genotype of the ELOVL3 gene in doe can be used as molecular markers for assisted selection of cashmere fineness. CCTG haplotype combination was the superior haplotype combinations for cashmere production performance. To provide a theoretical basis for the breeding and expansion of fine-fiber type new strains of LCG.